Zero-dimensional gold application in colorimetrically optimized ELISA signal enhancement for diagnosing osteoarthritis. (November 2022) - Li, Peng; Zhang, Bo; Gopinath, Subash C.B.; Subramaniam, Sreeramanan; Zhang, Jin
Abstract: Osteoarthritis (OA) is a degenerative disease affecting mainly the joints in articular cartilage. As OA progresses, biomarkers are collected in the synovial fluid and released into the blood. C-terminal telopeptide of type II collagen (CTX-II) is playing a major role in OA progression and proved CTX-II increment in the biological fluids to be an alarming for bone resorption and cartilage damage. Highly sensitive ELISA with zero-dimensional gold nanoparticle (GNP) mediated signal enhanced was introduced here to quantify CTX-II level. HRP-conjugated antibody was attached on GNP under the optimal conditions revealed by colorimetry, which increases the higher attachment on the ELISA well and subsequently elevated the signal. The detection limit of CTx-II at 0.1 ng/mL is two times lower than the signal obtained by the conventional ELISA. Further, CTX-II-spiked serum increases the signal upon increasing the concentrations of CTX-II and the limit of detection was calculated as 0.1 ng/mL with an R 2 value of 0.9858. Further, control performances with irrelevant proteins and non-immune antibody did not increase signal, indicating the specific detection of CTX-II. Graphical Abstract: ga1 Highlights: C-terminal telopeptide of typeII collagen (CTX-II) is in Osteoarthritis progression. ELISA with zero-dimensional gold enhanced signal and optimized calorimetrically. HRP-conjugated antibody was attached gold, reached the detection at 0.1 ng/mL. 2-fold higher sensitivity than conventional ELISA with Coefficient regression of 0.9858. CTX-II-spiked serum increases signal at limit of detection as 0.1 ng/mL & specific.